Pelaksanaan Pembelajaran Musik Talempong Pacik Di Kelas VIII-1 Smp Islam Al -Azhar Kota Padang - Hartono Hartono; Syeilendra Syeilendra (SENDRATASIK UNP, 2021)
This study aims to find out the ability of students at class VIII.1 in Padang city in playing Talempong Pacik with the song Cak Din Din. This research belongs to a descriptive qualitative research. The main instrument on this study was the researcher itself and was supported by supporting instruments such as writing tools and cameras. The data were collected through interview, literature study, and documentation. The data analysis was conducted by classifying the data, describing the data, and making conclusions. The results show that the students’ ability in playing Talempong Pacik with the song Cak Din Din is quite good after the learning process was evaluated. The assessment was obtained from the value of daily test results with assessment indicators including tempo and rhythmic accuracy as well as the students’ sense of musicality. The learning process was carried out in four meetings. In the fourth meeting, the learning evaluation was conducted. The learning activities were divided into three stages: preparation, process or training, and evaluation. The introduction of the song Cak Din Din was done by showing the song’s score and giving demonstrations by the teachers.